Vulnerabilidade cognitiva para depressão em crianças e adolescentes - Vanessa Maria de Almeida (2014)
Cognitive vulnerability to depression refers to the presence of dysfunctional cognitions, which allied with the experience of stressful events, would favor the emergence of depressive symptoms. This is a widely researched concept in adult samples. However, the data are not yet clear for children and adolescents. For the above reason, we conducted a literature review in order to verify a cognitive vulnerability to depression in this population. The databases Web of Science, MEDLINE, OneFile, American Psychological Association (APA), ScienceDirect, ERIC and PubMed Central were used in the search for articles. After their examination, 13 articles were included in the review. The results reported inconclusiveness about the presence of cognitive vulnerability and diathesis-stress paradigm in children and adolescents. One hypothesis is that at this age, dysfunctional cognitions are still forming. Given the information obtained through the review, we sought to conduct a longitudinal study that undertook to investigate the cognitive vulnerability to depression in children and adolescents. To this end, a sample of 225 individuals, aged between ten and 16 years old, who were assessed by the Inventário de Tríade Cognitiva para Crianças e Adolescentes (ITC-CA) and the Inventário de Depressão Infantil (CDI), was used. The participants were evaluated with the same instruments as well as the Inventário de Eventos Estressores na Infância e na Adolescência (IEEA) 8.4 months after the first evaluation. The results portrayed the importance of positive cognitions, in addition to negative cognitions, related to the self and the world for the prediction of depressive symptoms. In addition, subjects with negative cognitions above the 75 percentile, called vulnerable, facing high levels of stress had more severe rates of depressive symptoms than vulnerable individuals with the experience of stress in low and moderate levels. This result leads us to the possibility of the existence of certain threshold levels of stress in children and adolescents vulnerable to the onset of depressive symptoms. Suggestions for new studies from the data obtained are presented.